Preparation of former heavyweight oarsmen to compete as lightweight rowers over 16 weeks: Three case studies - Slater, G. J.; Rice, A. J.; Jenkins, D.; Gulbin, J.; Hahn, A. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
To strengthen the depth of lightweight rowing talent, we sought to identify experienced heavyweight rowers who possessed physique traits that predisposed them to excellence as a lightweight. Identified athletes (n = 3) were monitored over 16 wk. Variables measured included performance, anthropometric indices, and selected biochemical and metabolic parameters. All athletes decreased their body mass (range 2.0 to 8.0 kg), with muscle mass accounting for a large proportion of this (31.7 to 84.6%). Two athletes were able to maintain their performance despite reductions in body mass. However, performance was compromised for the athlete who experienced the greatest weight loss. In summary, smaller heavyweight rowers can successfully make the transition into the lightweight category, being nationally competitive in their first season as a lightweight.